Preparation of potent and selective αvβ6 integrin inhibitors for the treatment of idiopathic pulmonary fibrosis and synthetic approaches towards the total synthesis of mescengricin - Robinson, Henry Duncan (2021)
Idiopathic pulmonary fibrosis (IPF) is a terminal illness characterised by excessive build-up of scar tissue within the lungs. Despite a relatively high incidence amongst the population, there are no currently available treatments that prolong the estimated lifespan of an affected individual beyond approximately six years. Previous work has determined that inhibition of the αvβ6 integrin may yield positive results with regards to halting the progression of the disease and so much work has been focussed upon the development of selective αvβ6 integrin inhibitors. The work described in this thesis details the development of such inhibitors; first the preparation of potent and selective 3-monosubstituted β-3-aryl-amino acid derived analogues, of which a number performed well in additional drug metabolism and pharmacokinetics (DMPK) studies indicating potential oral bioavailability, followed by the combination of the most favourable structural features to yield a series of 3,5-disubstituted integrin inhibitor analogues. These latter analogues exhibited improved selectivity profiles and encouraging drug-like features and were viewed as a promising point from which to further progress the series, potentially resulting in the development of a clinical candidate. Following the halting of the integrin assays used to assess these inhibitor analogues, the total synthesis of mescengricin, a naturally occurring α-carboline containing molecule, was attempted, with the subsequent results from that work being detailed.